Pink and Say - Polacco, Patricia (New York : Philomel Books, 1994)
Chronicles the frienship of Pink, a fifteen-year-old African-American Union soldier, and Say, his poor white comrade, as one nurses the other back to health from a battle wound and the two of them are imprisoned at Andersonville. Based on a true story.
4.9
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Friendship -- Fiction; Historical fiction; Friendship -- Fiction; Historical fiction; United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction